Accuracy of self‐report of HIV viral load among people with HIV on antiretroviral treatment. Issue 7 (22nd December 2016) - Sewell, J; Daskalopoulou, M; Nakagawa, F; Lampe, FC; Edwards, S; Perry, N; Wilkins, E; O'Connell, R; Jones, M; Collins, S; Speakman, A; Phillips, AN; et al.
Abstract : Objectives: The aim of the study was to assess, among people living with HIV, knowledge of their latest HIV viral load (VL) and CD4 count. Methods: Agreement between self‐report and clinic record was assessed among 2771 HIV‐diagnosed individuals on antiretroviral treatment (ART) in the UK Antiretrovirals, Sexual Transmission Risk and Attitudes Study (2011–2012). A confidential self‐completed questionnaire collected information on demographic, socioeconomic, HIV‐related and health‐related factors. Participants were asked to self‐report their latest VL [undetectable (≤ 50 copies/mL), detectable (> 50 copies/mL) or "don't know"] and CD4 count (< 200, 200–350, 351–500 or > 500 cells/μL, or "don't know"). Latest clinic‐recorded VL and CD4 count were documented. Results: Of 2678 participants on ART, 434 (16.2%) did not accurately report whether their VL was undetectable. Of 2334 participants with clinic‐recorded VL ≤ 50 copies/mL, 2061 (88.3%) correctly reported undetectable VL; 49 (2.1%) reported detectable VL; 224 (9.6%) did not know their VL. Of 344 participants with clinic‐recorded VL > 50 copies/mL, 183 (53.2%) correctly reported detectable VL; 76 (22.1%) reported undetectable VL; 85 (24.7%) did not know their VL. Of 2137 participants who reported undetectable VL, clinic‐recorded VL was ≤ 50 copies/mL for 2061 (96.4%) and <1000 copies/mL for 2122 (99.3%). In analyses adjusted for gender/sexual orientation, ethnicity, age and time since starting ART, factors strongly associated with inaccurate self‐report of VL (including "don't know") included socioeconomic disadvantage [prevalence ratio (95% CI) for "not" vs . "always" having enough money for basic needs: 2.4 (1.9, 3.1)], poor English fluency [3.5 (2.4, 5.1) vs . UK born], nondisclosure of HIV status [1.7 (1.3, 2.1)], ART nonadherence [2.1 (1.7, 2.7) for three or more missed doses vs . none in the past 2 weeks] and depressive symptoms (PHQ‐9 score ≥ 10) [1.9 (1.6, 2.2)]. Overall, 612 (22.9%) of 2667 participants on ART did not accurately self‐report whether or not their CD4 count was ≤ 350 cells/μL. Conclusions: There is a high level of accuracy of a self‐report of undetectable VL in people on ART in the UK. Overall, accurate knowledge of personal VL level varied according to demographic, socioeconomic, HIV‐related and health‐related factors. Active identification of people who may benefit from increased levels of support and engagement in care is important.